Morbidity in Young Adult Literature: A Case Study in the Outsiders - Dahal, Arvind (Interdisciplinary Journal of Management and Social Sciences, 2020)
The inevitable and universal nature of death has made it a popular topic in Young Adult literature. While death recurs in these stories however, death in young adult novels is much darker and more complex. In this light, this paper discusses why is the issue of death in Young Adult fiction is still a safe place to discuss from the novel “The Outsiders”. It argues that the young adults find themselves in a state of morbid fear and realize that what for them is the site of joy and peace is a place of horror to the adults.